Arterio-Venous (AV) Fistula: Surgical outcome in College of Medical Sciences Teaching Hospital, Bharatpur, Chitwan - Shah, S; Maharjan, N; Chapagain, D; Shrestha, KG; Reddy, DJ (Journal of College of Medical Sciences-Nepal, 2013)
Aims Arteriovenous fistula is considered as reliable form of vascular access for hemodialysis in Chronic Kidney Disease (CKD) patients. We aim to evaluate prospectively, the outcome and primary failure rate of Arteriovenous fistula in 30 Chronic kidney Disease patients with Glomerular Filtration Rate (GFR) <30ml/min. Materials and methods This prospective study was conducted at the department of cardiothoracic and vascular surgery (CTVS), College of Medical Sciences, Bharatpur from May 2011 to May 2012. Thirty patients ranging from age 25 to 76 years with stage IV and V CKD, i.e. GFR below 30ml/min, were included in this study. Detailed physical examination including arterial pulses i.e. axillary, brachial, radial and ulnar and blood pressure in both upper limbs was recorded. Allens test was performed on every patient and left upper limb was used for AV fistula formation. Brachiocephalic fistula was made in 19 (63.33%), while radiocephalic fistula was made in 11 (36.67%) patients. Patients were evaluated post operatively, on outdoor basis, weekly for 6weeks. All patients were evaluated for the presence or absence of complications i.e. infection, hematoma, thrombosis, aneurysms and steal syndrome. Results The complication was primary failure in two patients. One male patient got secondary infection and one female patient got post operative hematoma leading to 6.66% primary failure of fistula. No other complications were noted. Conclusion Arteriovenous fistula is the gold standard for vascular access for hemodialysis in patients with deteriorating renal function and end-stage renal disease. It is designed to improve the effectiveness of dialysis with fewer risks and complications than other vascular accesses. This study gives the higher success rate of 93.33% and concludes that age should not be a limiting factor when determining candidacy for arteriovenous fistula creation and is the safe procedure. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-4, 1-6 DOI: http://dx.doi.org/10.3126/jcmsn.v8i4.8693